Vivencias de la sexualidad de religiosas de vida consagrada en Lima - Fernández Huapalla, Esther Luzmila (2022)
The general objective of this research was to understand the experiences of sexuality of consecrated religious in Lima city. A qualitative approach and a phenomenological design were used. Semi-structured interviews were conducted with nine religious of consecrated life from differents congregations residing in Lima. Among the most relevant findings are that the socialization and expression of sexuality prior to to joining their community were associated with taboo, limited to biological changes, prohibition to explore their bodies, and with an emphasis on care to prevent sexual violence and unwanted pregnancies. This is associated with the various transgressions experienced during childhood and adolescence, which are identified with a social pattern that is repeated, later, in ecclesiastical and study spaces when they are religious. In relation to their experiences after entering their community, it is recognized that during initial and ongoing formation there is a change in the meaning of their sexuality, which they understand as a life dedicated to the service of the Kingdom of God through the bonds with their sisters and people in the mission spaces.